THE EFFECT OF ELECTRONIC FOOD FOR PREGNANCY (E-FOCY) APPLICATION ON THE NUTRITION BEHAVIOR OF PREGNANT WOMEN IN THE RIAU ISLANDS COMMUNITY - Ridayani, Rita; Dewi Mey Lestanti Mukodri; Marella, Marella; Ristina Rosauli Harianja; Neni San Agustina Siregar (International Journal of Social Science, 2024)
Malnutrition is the cause of maternal and child death. One population that is very vulnerable to nutritional problems is pregnant women.This research method is quantitative research with a quasi-experimental design (Quasi Experimental) with a one group pretest and posttest design. The samples taken in this study were all 30 pregnant women in the second trimester who had their wombs checked at the Bugis Village Community Health Center. The results of the pre-test knowledge analysis between the control group and the intervention group showed a p-value of 0.867 (p<0.05), which means that there was no significant difference in the pre-test knowledge score between the control group and the intervention group. The results of the posttest analysis of knowledge between the control group and the intervention group showed a p-value of 0.000 (p<0.05). However, from the research results it was found that there were significant differences in attitudes and behavior between pregnant women who were given intervention using the E-FOCY application and those who were only given counseling from the KIA book. There was a significant increase in knowledge from the pre and post test results (p-value 0.000). However, in the intervention group the increase was higher than in the control group.